Transcriptome Profiling Analysis of the Testis After Eyestalk Ablation for Selection of the Candidate Genes Involved in the Male Sexual Development in Macrobrachium nipponense - Jin, Shubo; Fu, Yin; Hu, Yuning; Fu, Hongtuo; Jiang, Sufei; Xiong, Yiwei; Qiao, Hui; Zhang, Wenyi; Gong, Yongsheng; Wu, Yan (Frontiers in Genetics, 2021)
The eyestalk of crustacean species secrets many hormones, affected the process of reproduction, molting, metabolism of glucose and other function in crustaceans. In this study, important metabolic pathways and candidate genes involved in the male sexual development were identified through performing the transcriptome profiling analysis of testis after the ablation of eyestalk from Macrobrachium nipponense. The histological observations revealed that the testis development became vigorous after eyestalk ablation, indicating the hormones secreted by the eyestalk have negative effects on the testis development in M. nipponense. Transcriptome profiling analysis revealed that 1,039, 1,226 and 3,682 differentially expressed genes (DEGs) were identified between normal prawns (CG)vs single-side eyestalk ablation prawns (SS), SS vs double-side eyestalk ablation prawns (DS), and CG vs DS, respectively, indicating the ablation of double-side eyestalk has more significant regulatory roles on male sexual development than that of single-side ablation, which was consistent with the histological observations. Lysosome, Apoptosis, Glycolysis/Gluconeogenesis, and Insulin signaling pathway were the main enriched metabolic pathways in all of these three comparisons, and the important genes from these metabolic pathways were also selected. The qPCR verifications of 10 DEGs from these metabolic pathways were as the same as that of RNA-seq. The qPCR, in situ hybridization and RNAi analysis of Mn-NFkBα revealed that NFkBα has the positive regulatory effected on testis development. This study provided new insights on male sexual development in M. nipponense, promoting the studies on male sexual development in other crustacean as well.